Covid-19 Screening Technique Framework For University Students’ Admission - Waidah Ismail; Rabihah Md Sum; Azuan Ahmad; Rosline Hassan; Anvar Narzullaev; Hani Ajrina Zulkeflee; Razan Hayati Zulkeflee; Rimuljo Hendradi (Geoinformatics International, 2024)
Coronavirus disease 2019 (COVID-19) is a global pandemic. Clinical studies have shown that there was an association between COVID-19 and cardiovascular disease. The virus can directly induce myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism. In Malaysia, students will come back to University soon. The screening techniques framework is required to reduce the pandemic Covid-19 transmission among the students. In this manuscript, we present a new screening technique framework which is consists of temperature and heart rate measurements, movement tracking and risk assessment. Students will be given a questionnaire to stratify their risk into high, medium, and low risk. The temperature will be measured by using an infrared thermometer. The heart rate will be monitored only in those in high and lowrisk categories by using a smart bracelet. The students’ movement will be tracked by using a Wi-Fi based location technique. To avoid any privacy concerns, the location data will be extracted only if the student shared the location with the confirmed COVID-19 case. Lastly, the risk assessment is required in reporting if the infection occurs among students.